A educação musical nas práticas educativas de professores unidocentes: um estudo com egressos da UFSM - Spanavello, Caroline Silveira (2005)
The aim of this investigation was to understand the relationship between educational practices in music education developed by generalist teachers in school and their musical preparation in the context of a Bachelor of Education (Pedagogia) at Federal University of Santa Maria. The qualitative approach was adopted as the methodological choice because such approach allows the accomplishment of an interpretation of reality according to several data interconnected in a complex whole. The semi-structured interview was the main data collection instrument. Twenty generalist teachers were interviewed, and the transcriptions were analyzed constituting the main source of data presented and discussed in the final report. The study is divided into four chapters. The first chapter presents an overview about generalist teachers and their relationship with music education. In the second chapter, the focus is on the music preparation offered in the Bachelor of Education at Federal University of Santa Maria. The third chapter presents the educational practices in music education reported by the participant teachers. In the fourth chapter, some ideas from the two last chapters are articulated in a way to understand the relationship between preparation and practice. As a conclusion, there is an evident articulation between those two processes. However, it is perceived that the educational practices in music education are permeated not only by the knowledge built up since the initial preparation, but also by a series of factors, such as: the functional and organizational school structure, the school subjects historically considered more important than others, the parent s and the students demand considering their life history, anxiety and objectives of the teachers.